Novel BEST1 mutations and special clinical characteristics of autosomal recessive bestrophinopathy in Chinese patients. Issue 3 (28th December 2018) - Luo, Jingyi; Lin, Mingkai; Guo, Xinxing; Xiao, Xueshan; Li, Jiali; Hu, Huan; Xiao, Hui; Xu, Xiaoyu; Zhong, Yimin; Long, Shixian; Luo, Guangwei; Mi, Lan; et al.
Abstract: Purpose: The aim of this study was to describe the genetic and clinical characteristics of Chinese patients with autosomal recessive bestrophinopathy (ARB). Methods: This study presents a retrospective observational case series. Twenty‐one ARB patients and 25 clinically healthy family members were recruited. The coding regions and adjacent intronic regions of BEST1 were analysed via Sanger sequencing. Clinical examinations, including ultrasound biomicroscopy, A‐scan, optical coherence tomography, fundus autofluorescence, fundus fluorescein angiography (FFA), indocyanine green angiography (ICGA) and visual electrophysiology, were reviewed. Results: Six novel mutations (c.380C>T, p.T127M; c.397A>G, p.N133D; c.500A>G, p.E167G; c.817G>A, p.V273M; c.174_176del, p.Q58del; and c.950_955del, p.S318_L319) and 8 previously reported mutations were identified. The p.R255W mutation had the highest frequency in our cohort. Twenty patients had serous retinal detachment with multifocal subretinal vitelliform deposits in the posterior poles. One patient exhibited chorioretinal atrophy. FFA revealed peripheral vascular leakage in 10 patients, and ICGA revealed hyperfluorescent spots in 8 patients. Visual electrophysiology was abnormal in all patients. Fifteen patients with angle closure (AC) or angle‐closure glaucoma (ACG) had shallower anterior chambers and shorter axial lengths than the patients with open angle, contributing to their risk of developing AC/ACG. One patient developed AC during the 7‐year follow‐up period. The misdiagnosis and missed rates were 35.3% and 58.8%, respectively. Conclusion: The six novel mutations and high frequency of p.R255W suggest ethnical differences in the BEST1 mutation spectrum among Chinese patients. BEST1 gene screening and detailed clinical examinations help establishing a diagnosis of ARB. Clinical evaluations of the risk of developing AC/ACG are recommended for ARB patients.